Livro didático de história do 5º ano: um elemento socializador da violência - Rodrigues, Delweks (2009)
Violence dwells in human societies ever since the first groupings one knows of. It is argued, in this sense, that violence has been reproduced through the civilizing process. This is the premise we depart from in order to identify an element that might participate in the process of reproduction of violence. We chose 5th Grade History books as the object of research. The essence of a historic fact cannot be changed, but the ways one approaches and presents it are quite variable. We focus our attention, therefore, on ways of approaching historic themes and facts. The theoretical background is that of Psychoanalysis. Freud considers that the subject is evil by nature, a fact that constitutes one of the major barriers to social life. Such ideas are based on the theory of drives, which, according to Freud, explains the social and individual life. This is the model that informs the comparison we made between the concepts of culture and individual theorized by Freud and the models of culture and individual in the didactic books. We noticed that the History didactic books use the resources of projection (in the Psychoanalytical sense) and euphemism to soften violence in History. They are ultimately an element that both socializes and trivializes violence.